'Horace said, and so / Say I': Generic Transgression and Tonal Dissonance in Don Juan I, stanzas 212–16. Issue 2 (December 2017) - Caines, Karen
Abstract : In stanza 200 of Canto I of Don Juan, Byron famously declares 'My poem's epic […] / After the style of Virgil and of Homer'. Yet the passage in which Byron first unequivocally signals his deviation from the epic prototype deserves more detailed attention. For in stanzas 212–16 he turns not to his professed classical models, but, in a characteristically deliberate and disruptive act of generic transgression, to the Augustan poet Horace in introspective lyric mode. In style and content, Byron's reflections in this sequence on lost youth, premature ageing and dulled passions draw, for the greater part, directly on Horace's Odes 3.14 and 4.1. However, on revision, he adds a tonally dissonant, Romanticised recasting of the Horace framed in a higher emotional register, and then, as a climax to the stanza sequence, provocatively subverts Horace by an abrupt change of tone and a cynical proposal to abandon love for acquisitiveness.